I want to tell you my name : augmented reality as conservation method for between words and images by Ernestine White-Mifetu and Toni Giselle Stuart - McGinn, Isabelle (University of Pretoria, 2023)
Mini Dissertation (MSocSci (Tangible Heritage Conservation))--University of Pretoria, 2022.